Northwest History. Forest Fires (Cont'd). (1936)
Fierce Blaze Strikes Flathead near Kalispell. Fierce Blaze Strikes Flathead near Kalispell. Three hundred fire fighters, hurriedly recruited Sunday through the city employment agency by the forest service, were assembled at the city hall and rushed on special busses to Kalispell, Mont. The men are to reinforce crews on a new, fast-spreading forest fire in the Flathead national forest started by dry electrical storms Saturday night. Crews yesterday gained control of a dangerous fire in the scenic Seven Devils mountains in the Nez Perce national forest, west of Riggins, Idaho, after it had spread over more than 640 acres. Fire fighters managed to head off the blaze in a struggle made harder by areas of dry bear grass which swept the fire through the timber with almost explosive speed. High winds frustrated control attempts Saturday. Caused by Careless Smoker. More than 160 men were kept on patrol and mopping up work. The blaze, discovered by a lookout Friday, was believed started by a careless camper or smoker, and at one time threatened the entire Seven Devils district. Twenty new fires were reported in region No. 1 yesterday. Sixteen of these were started by scattered electrical storms and the remainder were man caused. Largest was a blaze in the Big Creek district of Flathead national forest which was being fought by a crew of 62 men. The same district also had six new small lightning fires. Other fires were as follows: Kootenai forest, two class A fires; Spotted Bear, Big Curly and Big Schaeffer districts of the Flathead forest, one class A fire each; Cabinet forest, three class A fires; Beaver creek district of Kaniksu forest, one class A; Coeur d'Alene forest, one class A. All fires were reported controlled late yesterday. All forests in region No. 1 were given high danger ratings except the Clearwater and Kaniksu. Rangers reported the first snow of the season fell Saturday night on Mosquito peak, northeast of Missoula, Mont., in the Lolo forest. Scattered showers were reported in other forest areas.